Diversité Et Abondance Des Micromammifères Terrestres: Indicateurs De L’anthropisation De La Forêt Classée De Monogaga, Sud-Ouest De La Côte d’Ivoire - Akpatou Kouamé Bertin; Bohoussou Kouakou Hilaire; Kadjo Blaise; N’goran Kouakou Eliezer; Adou Yao Constant Yves (European Scientific Journal, ESJ, 2018)
Anthropization of Classified Forests (CF) is a recurrent phenomenon in Côte d'Ivoire. It particularly affects coastal forests including Monogaga classified forest. Currently, flora composition and vegetation structure are the only biological tools available to better appreciate impacts of anthropic pressures on Monogaga classified forest. Yet, fauna and more particularly terrestrial small mammals constitute an essential component of this forest. Thus, this study aims to contribute to the understanding of the effects of anthropization of Monogaga classified forest based on "terrestrial small mammal" model. We used conventional Sherman traps to fairly investigate terrestrial small mammal communities in four plots (A, B, C and D) subjected to different anthropogenic pressures through Monogaga classified forest. Plots A and B were more disturbed than plots C and D. We collected 66 specimens in 1920 trap nights. These specimens are distributed among seven rodent species Dephomys defua, Hybomys trivirgatus, Hylomyscus simus, Lophuromys sikapusi, Malacomys edwardsi, Mastomys erythroleucus and Praomys rostratus and one soricomorph Crocidura olivieri. Abundances of terrestrial small mammals are higher in plots C and D. In the same way, diversity indices decrease from the most conserved to the least conserved plots. However, differences in species richness are weak between plots. Hierarchical classification of the four plots based on small mammal’s assemblages allows a good segregation. This study confirms that "terrestrial small mammal" model can contribute to the assessment of anthropization of forest habitats in lower Côte d'Ivoire.